2014
DOI: 10.3390/rs6087762
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating MERIS-Based Aquatic Vegetation Mapping in Lake Victoria

Abstract: Delineation of aquatic plants and estimation of its surface extent are crucial to the efficient control of its proliferation, and this information can be derived accurately with fine resolution remote sensing products. However, small swath and low observation frequency associated with them may be prohibitive for application to large water bodies with rapid proliferation and dynamic floating aquatic plants. The information can be derived from products with large swath and high observation frequency, but with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…For instance, in this study, it was found that NDWI and NDVI derived from low (300 m) MERIS images were generally higher over water surfaces than those generated from high-resolution (30 m) TM images. This finding is in accordance with [45], who found that MERIS had higher reflectance values over water surfaces in the green band compared to TM. Most studies [53][54][55] that make use of coarse-resolution optical imagery for flood mapping do not adequately account for the effects of mixed pixels.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For instance, in this study, it was found that NDWI and NDVI derived from low (300 m) MERIS images were generally higher over water surfaces than those generated from high-resolution (30 m) TM images. This finding is in accordance with [45], who found that MERIS had higher reflectance values over water surfaces in the green band compared to TM. Most studies [53][54][55] that make use of coarse-resolution optical imagery for flood mapping do not adequately account for the effects of mixed pixels.…”
Section: Discussionsupporting
confidence: 82%
“…This is done by assuming that the observed pixel-wise spectral reflectance is a linear combination of the spectral reflectance of soil, water and vegetation endmembers, then using the pixel-wise spectral reflectance to determine NDWI and NDVI. The assumption is that the different components in a pixel contribute independently to its reflectance [45]. The NDWI SU equation for the estimation of γ w is rewritten by substituting the (pixel) spectral reflectance values as linear combinations of the ones of the three endmembers, together with their abundances, where only γ w is unknown and can be determined from observed NDWI.…”
Section: Indices-based Spectral Unmixingmentioning
confidence: 99%
“…In addition, remote sensing can markedly decrease aquatic vegetation data acquisition costs. The satellite data used for these purposes include satellite multi-spectral moderate spatial resolution data (TM, ETM, MODIS, MERIS), satellite multi-spectral high-spatial resolution data (Quickbird 2), and airborne hyper-spectral (CASI 2) data 22 23 24 25 26 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Aside from conventional techniques, such as field mapping and photography, remote sensing can be an effective tool for mapping aquatic vegetation distributions over large scales. Many remote sensing techniques and methods, including spectral inversion, classification trees, the normalized difference vegetation index (NDVI), the floating algae index (FAI) and vegetation presence frequency (VPF), have been developed to accurately identify aquatic vegetation using different types of remote sensing imagery (TM, MODIS, MERIS and airborne data) 22 23 24 25 26 27 28 . In addition, long-term site-specific observations of water quality can generate long, data-rich time series and yield insights into the dynamics of water quality 6 29 .…”
mentioning
confidence: 99%
“…These plants may be free-floating or rooted in bottom sediment and submersed. However, on the other side, aquatic weed infestation is one of the major environmental challenges globally, threatening the integrity and functioning of most hydrological ecosystems (Cheruiyot et al, 2014). This invasion of foreign species leads to a number of ecological impacts, including reduced light and oxygen levels in the water column, which in turn reduces native macrophyte diversity.…”
Section: Introductionmentioning
confidence: 99%